Empowerment or Indoctrination? Female Training Programs under Dictatorship - Felipe González; Mounu Prem; Cristine von Dessauer (Institute of Labor Economics (IZA), 2024)
Autocrats often control social organizations to disseminate their ideology. We examine the Pinochet dictatorship in Chile (1973–1990), where conservative military forces controlled female social organizations to promote traditional roles for women as mothers and housewives. Partnering with higher education institutions, the dictatorship delivered training programs aimed at fostering domestic skills. Our findings reveal these programs facilitated women's entry into the labor market without changing their political views. Decades later, these programs are still linked to higher female labor force participation among women directly exposed during the dictatorship and their daughters raised in democracy.
Keywords: 330; women; centers; labor force participation; empowerment; dictatorship